Counselling in a multicultural society - Palmer, Stephen; Laungani, Pittu (London : Thousand Oaks, Calif. : Sage Pubications, 1999)
Addressing cultural issues as they relate to counselling & psychotherapeutic situations, this book sensitizes readers to the cultural & racial setting where counselling occurs, & aims to raise awareness of the needs of those from various cultures.
Includes bibliographical references (p. [204]-205) and index.
Keywords: Cross-cultural counseling; Psychiatry -- Transcultural; Cross-cultural counseling -- Great Britain